SLA-Based Injection Molding Tool Inserts: Challenges,Innovations, and Future Prospects - Tuteski, Ognen; Kochov, Atanas (Faculty of Technical Sciences, 2024)
Stereolithography (SLA), a key technology in additive manufacturing, has transformed the production of injection molding tool inserts by enabling rapid prototyping and cost-effective small scale production. SLA utilizes photopolymer resins to fabricate intricate, high-precision molds, reducing lead times and costs. However, challenges such as limited mechanical strength, lower thermal resistance, and slower heat dissipation compared to traditional materials constrain its broader adoption. This paper reviews the application of SLA in injection molding, emphasizing advancements in high-performance resins that improve durability, thermal stability, and mechanical properties. Key factors affecting mold performance, including material flowability, cooling times, and injection pressure, are discussed alongside optimization strategies like modular designs and post-processing techniques. While SLA molds may not rival traditional tools for high-stress applications, they excel in rapid tooling and prototyping. As material and process innovations continue, SLA is poised to play a transformative role in modern injection molding, bridging additive and traditional manufacturing.
Keywords: stereolithography; injection molding; additive manufacturing; rapid tooling